1982
DOI: 10.3758/bf03212282
|View full text |Cite
|
Sign up to set email alerts
|

Incentive contrast: A review of behavioral changes following shifts in reward

Abstract: The literature relevant to incentive contrast effects is reviewed, with emphasis on the data published since the reviews by Black (1968) and Dunham (1968). Contrary to the evidence available for the earlier reviews, the current literature indicates that positive contrast is a reliable phenomenon. Its occurrence is facilitated by use of a constant delay of reward, use of a long runway, or possibly by a shift while a negative contrast effect, resulting from a previous shift, is still present in the animals' beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
246
4

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(267 citation statements)
references
References 272 publications
17
246
4
Order By: Relevance
“…Last, it is worth noting that unblocking experiments bear at least a superficial similarity to instrumental incentive contrast experiments (see Flaherty, 1982, for a recent review). Subjects are trained with either large or small rewards in the first phase, and then the rewards are either shifted to the other reward value or maintained in the second phase.…”
Section: Discussionmentioning
confidence: 99%
“…Last, it is worth noting that unblocking experiments bear at least a superficial similarity to instrumental incentive contrast experiments (see Flaherty, 1982, for a recent review). Subjects are trained with either large or small rewards in the first phase, and then the rewards are either shifted to the other reward value or maintained in the second phase.…”
Section: Discussionmentioning
confidence: 99%
“…Procedurally, the positive contrast effect reported by Clement et al (2000) appears to be most similar to that involved in anticipatory contrast (Flaherty, 1982) because in each case there is a series of paired events, the second of which is better than the first. High effort is followed by discriminative stimuli in the case of the Clement et al procedure, and a low concentration of saccharin is followed by a higher concentration of sucrose in the case of anticipatory contrast.…”
Section: The Present Within-trial Contrast Effectmentioning
confidence: 75%
“…Furthermore, the behavior assessed is typically consummatory behavior rather than running speed. For example, rats often drink less of a weak saccharin solution if they have learned that it will be followed by a strong sucrose solution, relative to a control group for which saccharin is followed by more saccharin (Flaherty, 1982). This form of contrast differs from others in the sense that the measure of contrast involves differential rates of the consumption of a reward (rather than an independent behavior such as running speed).…”
Section: Anticipatory Contrastmentioning
confidence: 89%
See 1 more Smart Citation
“…To begin with, the findings seem relevant to the literature on incentive contrast-behavioral changes due to shifts in reinforcer value. Dozens of studies with a range of species have shown that downward shifts in reinforcer value induce predictable changes in behavior, including aggression and other behavior incidental to the reinforcement contingencies (Flaherty, 1982;Pellegrini et al, 2008). What is notable about these findings is that a reinforcer capable of sustaining behavior in its own right loses its value when contrasted with a higher-valued reinforcer.…”
mentioning
confidence: 99%